2001
DOI: 10.1073/pnas.031580798
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of glycine receptors expressed by embryonic rat brain mRNAs

Abstract: A study was made of glycine (Gly) and ␥-aminobutyric acid (GABA) receptors expressed in Xenopus oocytes injected with rat mRNAs isolated from the encephalon, midbrain, and brainstem of 18-dayold rat embryos. In oocytes injected with encephalon, midbrain, or brainstem mRNAs, the Gly-current amplitudes (membrane current elicited by Gly; 1 mM Gly) were respectively 115 ؎ 35, 346 ؎ 28, and 389 ؎ 22 nA, whereas the GABA-currents (1 mM GABA) were all <40 nA. Moreover, the Gly-currents desensitized faster in oocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A similar switch in glycine receptors was also found in brain stem motoneurons and in the substantia nigra (Mangin et al 2002;Singer et al 1998). In contrast, it has been reported that there is no evidence of a molecular switch in midbrain neurons (Garcia-Alcocer et al 2001). It is notable that subtypes of glycine receptors show different sensitivities to picrotoxin, a blocker of agonist-gated Cl Ϫ channels (Legendre 2001;Mangin et al 2002).…”
Section: Molecular Subtypes Of Glycine Receptorsmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar switch in glycine receptors was also found in brain stem motoneurons and in the substantia nigra (Mangin et al 2002;Singer et al 1998). In contrast, it has been reported that there is no evidence of a molecular switch in midbrain neurons (Garcia-Alcocer et al 2001). It is notable that subtypes of glycine receptors show different sensitivities to picrotoxin, a blocker of agonist-gated Cl Ϫ channels (Legendre 2001;Mangin et al 2002).…”
Section: Molecular Subtypes Of Glycine Receptorsmentioning
confidence: 98%
“…Therefore the most probable source of glycine as a neurotransmitter on DCN neurons is interneurons of the DCN, which may release pure glycine or glycine and GABA simultaneously. It is relevant in this regard to note the phenomenon of co-localization of GABA and glycine in the same terminal and changes in the neurotransmitter from GABA to glycine or vice versa at certain synapses during development or under some diseased conditions can occur (Gao et al 2001;Garcia-Alcocer et al 2001;Singer and Berger 2000;Sultan et al 2002;Turecek and Trussell 2002;Zhou et al 2002). Additionally, in the cerebellar cortex of the rat, pure and mixed glycinergic and GABAergic transmission has been proved elecrophysiologically in Golgi cells (Dumoulin et al 2001).…”
Section: Origin Of Glycinergic Innervation and Its Functional Rolesmentioning
confidence: 99%
“…Furthermore, a functional heterogeneity of GlyRs was found in the developing spinal cord where two different populations of GlyRs were distinguished by the size of their mRNAs and by the functional properties of the receptors expressed (Akagi et al, 1989; Morales et al, 1994). Molecular cloning of the genes encoding the GlyR subunits (α1–4 and β) allowed a determination of their individual contribution to the receptors in the brain and spinal cord as well as in several areas of the embryonic rat brain (Akagi et al, 1989; Charrier et al, 2006; García‐Alcocer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the rat brain embryo, we previously detected mRNA transcripts coding for the β subunit as early as E8 whereas transcripts coding for the α1–3 subunits were expressed from E13 onwards (García‐Alcocer et al, 2001). At developmental stage E13, cerebellar differentiation is incomplete, and the role of GlyRs early during ontogeny is still unknown.…”
Section: Introductionmentioning
confidence: 99%